PELATIHAN PENYUSUNAN INSTRUMEN PENILAIAN BERBASIS E-MODUL INTERAKTIF BAGI GURU DAN SISWA MI MUHAMMADIYAH SREBEGAN CEPER KLATEN - Banun Havifah Cahyo Khosiyono; Rahayu Retnaningsih; Krisna Aji Wibowo (Rafandha Press, 2023)
This Community Service activity was carried out with the aim of increasing the competence of teachers to develop an interactive E-module-based assessment instrument and the use of interactive E-modules for MI Muhammadiyah Srebegan Ceper Klaten students. The Community Service activity was carried out by the Education and Basic Education Research and Evaluation Study Program in collaboration with MI Muhammadiyah Srebegan Ceper Klaten on Saturday, July 23, 2022. The activity was carried out offline at MI Muhammadiyah Srebegan. The participants of the activity were teachers and students of MI Muhammadiyah. The implementation of the activity begins with the presentation of material by each of the 2 resource persons, followed by an experience sharing session by students of the UST Research and Evaluation Study Program and Basic Education who have worked as teachers in elementary schools, then discussions and questions and answers, and continued with the practice of preparing learning tools. independently. The results of this activity are that the activity runs smoothly, quite a lot of benefits are obtained by the participants, including getting additional knowledge related to good learning tools, as a material for self-introspection to correct previously prepared learning tools, teachers are able to practice directly in compiling assessment instruments based on E-modules are interactive and students are able to use interactive E-modules.